Denmark : Financial Sector Assessment Program; Technical Note; The Danish Mortgage Market; A Comparative Analysis. (IMF Staff Country Reports; Country Report, 2007)
This technical note presents a comparative analysis of the Danish Mortgage Market. It discusses the particularities of the regulatory framework of the Danish mortgage system. The note compares and contrasts mortgage financing in Denmark and in other European countries, looking both at the product side and at the funding side. Recent European regulatory evolutions, which could have potentially far-reaching consequences for the Danish mortgage system, are elaborated. The note also highlights the challenges faced by the Danish mortgage system.